Enhanced Antibacterial Activity of Lactoperoxidase–Thiocyanate–Hydrogen Peroxide System in Reduced-Lactose Milk Whey - Ahmad Ni’matullah Al-Baarri; Novia Tri Damayanti; Anang Mohamad Legowo; İsmail Hakkı Tekiner; Shigeru Hayakawa (International Journal of Food Science)
The product of the lactoperoxidase system (LPOS) has been developed as a preservative agent to inhibit foodborne bacteria, but its action was, heretofore, limited to several original compounds in milk. This research was conducted to analyze the application of the lactoperoxidase system against Escherichia coli in fresh bovine milk and its derivative products to determine the strength of antibacterial activity. Lactoperoxidase was purified from bovine whey using the SP Sepharose Big Beads Column. The enzymatic reaction involving lactoperoxidase, thiocyanate, and hydrogen peroxide was used to generate the antibacterial agent from LPOS. This solution was then added to milk, skimmed milk, untreated whey, reduced-LPO whey, reduced-lactose whey, and high-lactose solution containing E. coli at an initial count of 6.0 log CFU/mL. LPOS showed the greatest reduction of bacteria (1.68 ± 0.1 log CFU/mL) in the reduced-lactose whey among the products tested. This result may lead to a method for enhancement of the antimicrobial activity of LPOS in milk and derived products.